2012
DOI: 10.1111/j.1476-5381.2011.01686.x
|View full text |Cite
|
Sign up to set email alerts
|

Low dose of propranolol down‐modulates bone resorption by inhibiting inflammation and osteoclast differentiation

Abstract: BACKGROUND AND PURPOSEBones are widely innervated, suggesting an important role for the sympathetic regulation of bone metabolism, although there are controversial studies. We investigated the effects of propranolol in a model of experimental periodontal disease. EXPERIMENTAL APPROACHRats were assigned as follows: animals without ligature; ligated animals receiving vehicle and ligated animals receiving 0.1, 5 or 20 mg·kg -1 propranolol. After 30 days, haemodynamic parameters were measured by cardiac catheteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
68
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 52 publications
13
68
0
1
Order By: Relevance
“…[16][17][18] Rodrigues et al demonstrated that low doses of PRO suppress bone resorption by inhibiting receptor activator of nuclear factor kappa-B ligand (RANKL)-mediated osteoclastogenesis as well as inflammatory markers without affecting hemodynamic parameters. 19 This result is supported by a previous finding, which showed that propranolol stimulates osteoprotegerin (OPG) on its own in osteoblast cells. 20 The ability to stimulate osteoblast, while also damping osteoclasts makes PRO an attractive and unique alternative to antiresorptive therapy for osteoporosis.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…[16][17][18] Rodrigues et al demonstrated that low doses of PRO suppress bone resorption by inhibiting receptor activator of nuclear factor kappa-B ligand (RANKL)-mediated osteoclastogenesis as well as inflammatory markers without affecting hemodynamic parameters. 19 This result is supported by a previous finding, which showed that propranolol stimulates osteoprotegerin (OPG) on its own in osteoblast cells. 20 The ability to stimulate osteoblast, while also damping osteoclasts makes PRO an attractive and unique alternative to antiresorptive therapy for osteoporosis.…”
Section: Introductionsupporting
confidence: 89%
“…PRO, which could directly prevent bone loss and biomechanical alteration by increasing bone formation and decreasing bone resorption, may be the next anabolic agent for osteoporosis treatment after PTH. 7,8,10,19,20 As immobilization induced bone loss involves both increased bone resorption and decreased bone formation, it seems to be obvious to target the immobilization induced bone loss with a combined antiresorptive and bone anabolic treatment regimen, such as ZOL and PRO. The effects of a combined PRO and ZOL treatment have previously been studied in ovariectomized rats, 7 whereas this treatment regimen has not previously been investigated in immobilization-induced osteopenia.…”
Section: Introductionmentioning
confidence: 99%
“…These molecular findings may explain the lower bone resorption observed in the treated groups, especially at a dose of 10 mg/kg. Interactions between the immune system and bone cells appear to be mediated by inflammatory cells and their related mediators, including cytokines and chemokines, which are able to regulate various inflammatory bone conditions (32,37). In this study, concomitantly with the control of RANKL expression and bone resorption, 15d-PGJ 2 -NC also inhibited leukocyte influx, which had a positive impact on bone resorption prevention.…”
Section: Discussionmentioning
confidence: 55%
“…The identification of RANKL, its receptor RANK, and the soluble decoy receptor OPG has contributed significantly to the understanding of the skeletal remodeling mechanism involved in the osteoclastogenesis process (29). Considerable efforts are being made to identify drugs able to inhibit RANKL or increase OPG, to adjust the RANKL/OPG ratio in several diseases (30)(31)(32), as well as to develop the use of human OPG constructs, which can powerfully inhibit bone resorption (33,34). More recently, a fully human mAb that binds and inhibits RANKL, called denosumab (AMG 162), was suggested as a promising drug able to reduce biochemical markers of bone resorption (35) in patients with multiple myeloma or bone metastases (36).…”
Section: Discussionmentioning
confidence: 99%
“…Findings suggest that the pharmacological antagonism of b2 receptors, like genetic ablation studies, cause anabolic effects on bone, which are much more pronounced in situations that favor bone loss, such as gonadectomy, low doses of propranolol or unloading [62,66]. According to the results obtained in b-hydroxylase mouse models, when mice are treated with a non-selective beta blocker, propranolol, they show an increase in bone mass [23,[67][68][69] and improved fracture healing [70]. Baek et al [71] found that using this antagonist attenuates the decline in trabecular mass in mice fed on high-calorie diets.…”
Section: Pharmacological Analyses In Animalsmentioning
confidence: 89%